Does Crop Species Diversity Influence Soil Carbon and Nitrogen Pools?. (1st January 2016) - Chatterjee, Amitava; Cooper, Kelly; Klaustermeier, Aaron; Awale, R.; Cihacek, Larry J.
Abstract : Crop species composition and richness exert a strong influence on soil C and N dynamics through the proportion of decomposable organic compounds returned to the soil. Under no‐till, soil C and N pools were compared for five crop rotations, (1) continuous corn ( Zea mays L.; CC), (2) spring wheat ( Triticum spp.)–soybean [ Glycine max (L.) Merr.; SW–S], (3) spring wheat–corn–soybean (SW–C–S), (4) spring wheat–winter wheat–corn–soybean (SW–WW–C–S), and (5) spring wheat–winter wheat–flax ( Linum usitatissimum L.)–corn–corn–soybean (SW–WW–F–C–C–S), in the northern Great Plains. Soil organic matter (SOM) content was highest under C–C and significantly higher than SW–WW–C–S ( P < 0.05). Highest organic C, C/N ratio and potentially mineralizeable carbon pool (PMC) was observed under SW–C–S rotation, similar to CC and significantly greater than SW–WW–F–C–C–S. Pearson correlation coefficients indicate rotation length had negative relationship with PMC; whereas, PMC had positive relationship with soil organic carbon (SOC) and C/N ratio. Increasing rotation length might increase the substrate diversity that reduces decomposition rate. Similar soil C and N pools of CC and SW–C–S rotations with annual fertilizer N inputs of 220, 111 kg N ha −1 yr −1, respectively, indicate SW–C–S rotation can be a potential alternative to CC to minimize the fertilizer N input and maintaining species diversity.